Efektivitas Media Edukasi Interaktif Berbasis Smartphone terhadap Pencegahan Anemia pada Remaja - Zulfitrawati Zulfitrawati; Dien Abdul Munir; Nina Isywara Kusuma; Abd Kadir S (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Anemia iremains ia icritical ipublic ihealth iissue iamong iadolescents, inecessitating ieducational imethods ithat iare iengaging, itechnologically irelevant, iand ieasily iaccessible. iThis istudy iaims ito iexamine ithe ieffectiveness iof iusing ismartphone-based iinteractive ilearning imedia iin iimproving iknowledge iand ianemia iprevention ibehavior iamong iadolescents. iUsing ia ipre-experimental idesign iwith ia ione-group ipretest-posttest iapproach, ithis istudy iwas iconducted iat iSMA iNegeri i12 iMakassar ifrom iMarch ito iApril i2026. iA itotal iof i60 istudents iaged i15–18 iyears iwere iselected iusing ipurposive isampling iand ireceived ian iintervention iin ithe iform iof ismartphone-based iinteractive ieducation ifor ifour iweeks. iData iregarding iknowledge iand ibehavior iwere iobtained ithrough ivalidated iand ireliable iquestionnaires iand iwere isubsequently ianalyzed iusing ithe iPaired iSample it-Test. iThe iresults ishowed ia isignificant iincrease iin ithe imean iknowledge iscore ifrom i62.40 ito i84.70 i(p=0.000), iand iin ithe ibehavior iscore ifrom i58.60 ito i79.20 i(p=0.000). iIn iconclusion, ismartphone-based iinteractive ieducational imedia iis iproven ieffective iin ienhancing iknowledge iand ianemia iprevention iactions; itherefore, iit iis irecommended ito ibe iintegrated iinto ischool ihealth ipromotion iprograms ias ia isustainable istrategy